(untitled) (Physical Education, Health and Social Sciences, 2025)
Despite the provisions in the constitution and international human rights commitments, historically discriminated people in Pakistan women, religious and ethnic minorities, persons with disabilities and low-income populations continue to experience systemic discrimination, social exclusion, and inaccessibility of basic services. The study objectives are: To discover the role of social workers in encouraging human rights advocacy among the marginalized communities in Sargodha, Punjab. To evaluate the usefulness of social work advocacy in enhancing access to services, rights awareness and social inclusion in the marginalized groups. To determine structural, institutional and socio-cultural dispositions that constrain social work participation in human rights advocacy in the Sargodha, Punjab. To present effective suggestions that can be made to enhance rights-based social work practice, policy support, and community empowerment in Sargodha, Punjab. The research design employed in the study was a quantitative cross-sectional investigation that examined the relevance of social work in enabling the needy communities in Pakistan to advocate human rights. The study was carried out in Sargodha District, Punjab, Pakistan, whereby it is characterized by mixture of urban, rural and peri urban community and in addition, there is a high level of socio-economic disparity. The reason behind choosing Sargodha is that the location has a population of those people who are under marginalization like the low income families, women with gender exclusion, individuals with disabilities, religious and ethnic minorities and the informal settlements. The sample population was the individuals aged 18 years and above who are the members of the marginalized communities, who live in Sargodha District. Marginalization was defined as being poor, subjected to discrimination based on gender, disability, minority status, displacement, or access to basic services poorly. The research was conducted in a total of 380 respondents. The purposive sampling was applied to choose the respondents who have the firsthand experience of social exclusion and in necessary cases, the experience on social work advocacy services. The face to face interviews were conducted to collect information with the help of trained research assistants who were anticipated to ensure the clarity, accuracy as well as inclusiveness of information in particular in respondents who had low literacy levels. The data obtained were coded and analysed using the SPSS (Version 26). To test the study hypothesis and analyze the relationship between variables, they applied Chi-square tests to establish the relationship between human rights results and social work advocacy. The criterion of statistical significance was p < 0.05.